2016
DOI: 10.20884/1.anprod.2016.18.1.516
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sugarcane Bagasse as Animal Feed by Ammoniation and Followed by Fermentation with Trichoderma harzianum (In Vitro Study)

Abstract: Abstract. Sugarcane bagasse is one of agro-industrial residues containing low nutrient content and difficult to be digested by animals. However, it can be recycled to produce value-added product such as protein-enriched animal feed by application feed technology such as ammoniation and fermentation. The purposes of these experiments were to evaluate the quality and in vitro digestibility of sugarcane bagasse by using two steps feed technology process: ammoniation and continued by fermentation process. Two stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
2
5
0
5
Order By: Relevance
“…The result of the study indicated that fermentation improved IVDMD, IVOMD and reduced the content of NDF and ADF of sago residues ( Table 1). The results of this study were in accordance with the research conducted by Samadi et al (2016) in which sugarcane bagasse fermented with Trichoderma harzianum significantly increased IVDMD and IVOMD. Availability of soluble carbohydrates due to fermentation process was the cause of better IVDMD and IVOMD values.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The result of the study indicated that fermentation improved IVDMD, IVOMD and reduced the content of NDF and ADF of sago residues ( Table 1). The results of this study were in accordance with the research conducted by Samadi et al (2016) in which sugarcane bagasse fermented with Trichoderma harzianum significantly increased IVDMD and IVOMD. Availability of soluble carbohydrates due to fermentation process was the cause of better IVDMD and IVOMD values.…”
Section: Discussionsupporting
confidence: 91%
“…Utilization of crop residues from agro-industry byproducts as animal feed is one of the solutions to reduce feed cost. However, nutritive values and digestibility of feed using agro-industry byproducts were low and need several methods to be applied for improving the quality and digestibility of feed (Wanapat et al, 2009;Santoso et al, 2014;Wajizah et al, 2015;Samadi et al, 2015;Samadi et al, 2016;Wiryawan et al, 2017). Feed fermentation technology by microbial administration seems to be a practical and promising alternative to increase nutritional values of agro-industry residues and produce improved value-added products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini mungkin disebabkan karena lama waktu fermentasi yang relatif singkat selama satu minggu pada proses fermentasi awal sehingga tidak akan mempengaruhi kandungan NDF dari PT, yang selanjutya juga tidak berpengaruh terhadap degradasi in sacco. Hal ini sejalan dengan hasil penelitian Samadi et al (2016) bahwa fermentasi bagase tebu sampai 28 hari memberikan pengaruh yang tidak nyata terhadap kandungan serat kasar disebabkan karena kuat dan sangat kompleknya ikatan selulosa dan lignoselulosa. Kemungkinan lain adalah disebabkan karena jumlah atau level penggunaan T. harzianum masih terlalu kecil sehingga relatif belum mampu untuk meningkatkan degradasi NDF selama inkubasi.…”
Section: Degradasi Neutral Detergent Fiberunclassified
“…Perlakuan awal terhadap bahan pakan telah mendapatkan perhatian baru dan perhatian segar dari para peneliti karena pentingnya dalam perkembangan terakhir dalam konservasi energi biomassa, dalam pengolahan limbah padat dan dalam aplikasinya untuk menghasilkan metabolit sekunder (Bisaria et al 1997;Kamra et al 2000;Tang et al 2008;Wanapat et al 2009;Rahman et al 2011;Shrivastava et al 2011;Ginting 2012;Wajizah et al 2015;Samadi et al 2016). Fermentasi solid-state dapat menghasilkan bahan pakan alternatif denngan nilai gizi yang lebih baik kualitasnya.…”
unclassified